Medicinal Plants Used by Raji Ethnic Tribe of Nepal in Treatment of Gastrointestinal Disorders - Thapa, Lal Bahadur; Dhakal, Til Maya; Chaudhary, Raghunath; Thapa, Himanchal (Our Nature, 2014)
A total of 43 plant species belonging to 40 genera and 29 families have been recorded as medicinal plants used traditionally by Raji people of Nepal for treatment of gastrointestinal disorders. Different parts of medicinal plants in different forms were reported to be used for treatment of 16 types of gastrointestinal disorders. The traditional healers and elderly people were well experienced in traditional method of using medicinal plants but they were worried about negligence of people towards such traditional use of valuable medicinal plants. DOI: http://dx.doi.org/10.3126/on.v11i2.9645 Our Nature 2013, 11(2): 177-186